The professional [large type] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2009)
Elizabeth Shaw specializes in wills and trusts at the Boston law firm of Shaw & Cartwright, and over the years she's developed a friendship with wives of very wealthy men. However, these rich wives have a mutual secret: they've all had an affair with a man named Gary Eisenhower--and now he's blackmailing them for money. Shaw hires Spenser to make Eisenhower "cease and desist," so to speak, but when women start turning up dead, Spenser's assignment goes from blackmail to murder.